2020
DOI: 10.1177/2167702620902118
|View full text |Cite
|
Sign up to set email alerts
|

Using Positive Emotion Training With Maltreated Youths to Reduce Anger Bias and Physical Aggression

Abstract: Maltreated youths often overinterpret anger in others’ emotional expressions, particularly expressions that are ambiguous, and this “anger bias” is associated with aggressive behavior. In the current experiment, we tested the effect of an emotion-training intervention on anger bias and subsequent aggression. Eighty-four youths, ages 8 to 17, who had been removed from home because of maltreatment and had screened positive for aggressive tendencies, served as participants. Over 4 days, youths completed positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Richaud and Mesurado [35] found that positive emotions inhibit aggressive behavior. Furthermore, it has been shown that positive emotion training successfully reduces aggressive behavior [36]. Empirical evidence suggests that positive emotions can play an important role in preventing actions that harm others.…”
Section: Upward Assimilative Emotions and Behavioral Responsesmentioning
confidence: 99%
“…Richaud and Mesurado [35] found that positive emotions inhibit aggressive behavior. Furthermore, it has been shown that positive emotion training successfully reduces aggressive behavior [36]. Empirical evidence suggests that positive emotions can play an important role in preventing actions that harm others.…”
Section: Upward Assimilative Emotions and Behavioral Responsesmentioning
confidence: 99%
“…Identifying individuals who would benefit most from intervention is crucial as well. Because the mechanisms identified in the present study are likely to be relatively entrenched by the time an individual reaches adulthood, intervening earlier in development (e.g., during adolescence; see Dickerson, Skeem, Montoya, & Quas, 2020) may be advantageous. Furthermore, negative emotionality appears important for contextualizing the association between physical aggression and postdecisional processing of social threat (see Table S1 in the Supplemental Material), which suggests that interventions targeting negative emotionality might be useful.…”
Section: Discussionmentioning
confidence: 94%
“…Third, research by Dickerson et al demonstrated that positive emotional training can successfully reduce aggressive behavior. 65 To reduce the painful experience of envy and undermining behavior, 37 managers can provide emotion management training to improve employees’ emotional management capabilities. This will help employees learn to detect, understand and express emotions, release psychological pressure and negative emotions in an appropriate way, master positive emotional management and adaptation strategies, maintain a positive and optimistic mentality, and respond positively to upward social comparison.…”
Section: Discussionmentioning
confidence: 99%